Effect of capital structure on economic success of the DSE-listed firms in Bangladesh: A moderating role of COVID-19 pandemic - Islam, Md. Rabiul; Hossain, Syed Zabid; Wu, Renhong (Asian Development Policy Review, 2025)
A firm's prudent use of debt and equity is an essential indicator of robust financial management. The study empirically evaluated the impact of capital structure (CS) on the economic performance of Bangladeshi companies from 2010 to 2022. It uses data from 1300 observations collected from 100 DSE-listed firms from 10 leading sectors of the economy. The outcome variables included ROE, ROA, EPS, and Q ratios. The explanatory variables were the capital structure proportions of short-term liabilities (STL), long-term liabilities (LTL), and the firm growth rate. The firm size was regarded as the control variable. The regression results revealed that STL negatively impacted ROA, ROE, and, most remarkably, EPS, while STL failed to impact Tobin's Q. LTL, on the other hand, had a positive impact on EPS and a negative impact on Tobin's Q, indicating that Bangladeshi firms do not exhibit overvaluation. STL and LTL positively impacted corporate financial performance during the pandemic compared to the pre-pandemic period. The implications of these findings are crucial for policymakers and corporate leaders. Organizations must demonstrate caution when employing short-term liabilities, especially during stable periods. This study underscores the imperative for industry-specific strategies concerning capital structure, as sectoral differences affect leverage outcomes.